Students' mobility attitudes and sustainable transport mode choice. Issue 5 (2nd July 2018) - Cattaneo, Mattia; Malighetti, Paolo; Morlotti, Chiara; Paleari, Stefano
Abstract : Purpose: This study aims to explore the propensity of university students to use different sustainable transport modes, taking into account individual and specific trip characteristics, as well as students' psychological traits (i.e. attitudes). Design/methodology/approach: Using the transport mode preferences of 827 students who responded to a travel survey, a two-step analysis is conducted. The first step examines the effects of individual characteristics, travel experience and origin or destination features on students' stated preferences (i.e. self-selected values assigned to personal attitudes). The second step analyses students' travel mode choices, given their intrinsic mobility attitudes. Findings: The results suggest that informing students about environmental issues increases their propensity to use sustainable mobility, leading to an average decrease in private transport usage of 5.8 per cent. Interestingly, improving the public transport service and promoting sustainable transport mobility have different impacts on individual campus areas. For campuses located in the city centre and in the historical hamlet, improvements in public transport are found to decrease solo driving by 3.3 per cent and 5.3 per cent, respectively. In suburban areas, this value increases to 9.5 per cent. Originality/value: This work makes two contributions to the literature. First, it focuses on an unexplored setting, namely, that of a multi-campus university, with districts located in three different areas. This is used to explain how students are influenced by their travel experience and the cultural framework in which they are embedded. Second, the two-step analysis leads to a deeper understanding of the differences between attitudes and "intrinsic attitudes", and their relative influence on the preferred alternative.